2009
DOI: 10.1158/0008-5472.can-08-0946
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of a Combined 5-Aza-2′Deoxycytidine and Valproic Acid Treatment on Rhabdomyosarcoma and Medulloblastoma in Ptch Mutant Mice

Abstract: Patched (Ptch) heterozygous mice develop medulloblastoma (MB) and rhabdomyosarcoma (RMS) resembling the corresponding human tumors. We have previously shown that epigenetic silencing of the intact Ptch allele contributes to tumor formation in this model. Here, we investigated whether targeting of epigenetic silencing mechanisms could be useful in the treatment of Ptch-associated cancers. A reduction of endogenous DNA methyltransferase1 (Dnmt1) activity significantly reduced tumor incidence in heterozygous Ptch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 44 publications
1
85
1
1
Order By: Relevance
“…5-aza-2 0 -deoxycytidine, a standard DNMT inhibitor, and 400 mg/kg b.w. valproic acid, a standard HDAC inhibitor, have been reported to cause a moderate reversible leukocytopenia in mice (43). In yet another study performed in rats, the combinations of 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…5-aza-2 0 -deoxycytidine, a standard DNMT inhibitor, and 400 mg/kg b.w. valproic acid, a standard HDAC inhibitor, have been reported to cause a moderate reversible leukocytopenia in mice (43). In yet another study performed in rats, the combinations of 20 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of DNA methyl transferases 5-azacytidine (azacitidine) and 5-aza-2'-deoxycytidine (decitabine) had increased antitumor effects when used with HDAC inhibitors [60][61][62][63][64] . Decitabine and VPA both induced apoptosis and the combination increased their effects both in vitro and in vivo 65,66 . Co-treatment of prostate, pancreatic tumor, acute myelogenous leukemia (AML) AML1/ETO-positive and non small cell lung cancer (NSCLC) cells with trichostatin A and decitabine synergistically induced apoptosis 63,64,67,68 .…”
Section: Combination Of Histone Deacetylase Inhibitors With Other Thementioning
confidence: 99%
“…An in vitro experiment showed that the DNMT inhibitor 5-aza-2'-deoxycytidine (decitabine) reactivates the tumor suppressor PTCH1 gene in the MB cell line [4]. A combination of DNMT and histone deacetylase (HDAC) inhibitors was effective to prevent MB development in Ptch knockout mice, while in advanced stage tumors this therapy was less efficient [5]. Epigenetic modulators combined with multi-kinase inhibitor could enhance apoptosis in vitro in medulloblastoma cells [24].…”
Section: Discussionmentioning
confidence: 99%